Sodium hypochlorite in the priming of tobacco seeds - Lopes,Camila Aparecida (2019)
Abstract: Due to the non-uninform maturation of tobacco fruits and seeds, the priming technique has been used by the tobacco industry as a way of increasing the uniformity and germinations peed of seeds. Several factors can affect priming, including the time and environment in which the treatment is performed. In order to evaluate the effect of sodium hypochlorite as priming agent at different concentrations and the priming period on the physiological quality of the tobacco seeds, it was used a seed lot of commercial cultivar CSC 439 from the Virginia varietal group, widely used by the producing companies. The seeds were subjected to priming in aerated solution at different priming periods (180, 60, 30, 15, and 5 min) and concentrations of sodium hypochlorite (1%, 0.50%, 0.25%, and 0.10 %). The physiological quality was evaluated by the water contents, germination tests, first count, germination index, initial and final stands, emergence index and electrical conductivity. The priming with sodium hypochlorite did not affect germination, but allowed a higher percentage and speed of emergence when using the 1% concentration for 180, 30 and 15 min.